Mechanisms and Regulation of Aerobic Respiration in Shewanella Oneidensis MR-1 - (:unkn) unknown (My University, 2020)
Shewanella oneidensis MR-1 expresses three terminal oxidase complexes predicted to participate in aerobic respiration: an aa3-type cytochrome c oxidase, a cbb3-type cytochrome c oxidase, and a bd-type quinol oxidase. An intermediate bc1 complex is used for transfer of electrons to the aa3-type and cbb3-type cytochrome c oxidase complexes. Use of the terminal aerobic oxidases in S. oneidensis is atypical. The aa3-type cytochrome c oxidase is the expected primary oxidase complex in oxygen-replete conditions; however, it has no observed function in aerobic growth in S. oneidensis. The cbb3-type cytochrome c oxidase and bd-type quinol oxidase are the primary oxidases used for aerobic respiration in this organism, regardless of oxygen tension. The regulatory systems CRP, a cyclic AMP (cAMP) binding protein, and the ArcAB two-component system regulate anaerobic respiration and appear to play a role in aerobic growth if S. oneidensis. Furthermore, the S. oneidensis the cyclic AMP phosphodiesterase, cpdA (SO_3901) also appears to affect aerobic growth, but its exact role in this process is not known. . This work analyzes aerobic growth of mutants deficient in terminal oxidase complexes and regulatory proteins when exposed to different sole carbon sources in basal medium. A deletion mutant of both the bc1 complex and the bd-type quinol oxidase exhibited a severe growth deficiency under all conditions tested. Mutants deficient in CRP and ArcA demonstrated slight aerobic growth deficiencies. The cpdA mutant demonstrated a severe growth deficiency. Carbon source does not drastically affect the growth phenotype of mutants tested. In this work, aerobic growth of two CRP-like proteins (SO_2550 and SO_2551) was also analyzed. These proteins contain the cyclic nucleotide binding domain as well as the helix-turn-helix motif of CRP-family proteins. Deletion of genes that encode these proteins results in an aerobic growth deficiency. We also analyzed promoter expression of the two major aerobic terminal oxidase complexes in these regulatory protein deletion mutants. To assess promoter expression over time, a fluorescent timer system was developed using a mutant mCherry that fluoresces blue after translation and matures to red. This system allows analysis of growth and promoter expression simultaneously. Promoter expression did not drastically change during the growth cycle of S. oneidensis, confirming that growth deficiencies of regulatory system mutants are not due to lack of expression of terminal oxidase complexes. Recovery of the growth deficiency of the cpdA deletion mutant was also analyzed in this work. Addition of casamino acids to a basal medium restored aerobic growth in this mutant. Growth of a cpdA deletion mutant was also restored by the inactivation of SO_3550 (an anti- sigma factor). The SO_3550 cognate sigma factor encoded by SO_3551 is an ECF, or extracytoplasmic function sigma factor. ECF sigma factors are typically used in stress response in bacteria, suggesting that the action of this sigma factor is able to remedy the growth deficiency of the cpdA mutant.